2019
DOI: 10.1073/pnas.1820414116
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of APOL1 kidney disease risk variants to lipid droplets attenuates cell toxicity

Abstract: Two coding variants in the apolipoprotein L1 (APOL1) gene (termed G1 and G2) are strongly associated with increased risk of nondiabetic kidney disease in people of recent African ancestry. The mechanisms by which the risk variants cause kidney damage, although not well-understood, are believed to involve injury to glomerular podocytes. The intracellular localization and function of APOL1 in podocytes remain unclear, with recent studies suggesting possible roles in the endoplasmic reticulum (ER), mitochondria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 43 publications
5
67
0
3
Order By: Relevance
“…e APOL1 risk alleles activate the protein kinase R (PKR) which in turn induces glomerular injury and proteinuria [7]. Moreover, the APOL1 may function similarly to the LD-associated protein CIDEA, which has an amphipathic helix that facilitates embedding in the phospholipid monolayer and binding to phosphatidic acid, and altered association of APOL1 with LDs may alter APOL1 delivery to mitochondria, possibly controlling cytotoxicity [8].…”
Section: Introductionmentioning
confidence: 99%
“…e APOL1 risk alleles activate the protein kinase R (PKR) which in turn induces glomerular injury and proteinuria [7]. Moreover, the APOL1 may function similarly to the LD-associated protein CIDEA, which has an amphipathic helix that facilitates embedding in the phospholipid monolayer and binding to phosphatidic acid, and altered association of APOL1 with LDs may alter APOL1 delivery to mitochondria, possibly controlling cytotoxicity [8].…”
Section: Introductionmentioning
confidence: 99%
“…We tested whether ER stress could provide a stimulus to alter stress response and cellular phenotypes in the high-risk genotype. ER stress was chosen because ubiquitin D, encoded by UBD, is involved in the ER stress response, and risk-variant APOL1 appears to localize to the ER membrane 30 . Furthermore, ER stress is becoming an increasingly recognized driver of complex diseases, including CKD [31][32][33][34] .…”
Section: Resultsmentioning
confidence: 99%
“…We tested whether ER stress could provide a stimulus to alter stress response and cellular phenotypes in the highrisk genotype. ER stress was chosen because ubiquitin D, encoded by UBD, is involved in the ER stress response, and risk-variant APOL1 appears to localize to the ER membrane (36). Furthermore, ER stress is becoming an increasingly recognized driver of complex diseases, including CKD (37-40).…”
Section: Er Stress Induces Differential Expression Of Stress Responsementioning
confidence: 99%
“…Unlike prior models (25,45), our model system does not lead to much cell death in the G1 kidney organoids at 24 hours, nor does it activate many proapoptotic genes, consistent with the concept that another stressor is needed to induce a phenotype. We chose ER stress as an experimental condition because previous studies have indicated that risk-variant APOL1 may be regulated by UBD (32), a gene involved in the ER stress response, and that risk-variant APOL1 localizes to the ER rather than to lipid droplets (36). Expression of risk-variant APOL1 alone does not activate a significant unfolded protein response (as seen in Figure 5B), but some differences can be seen for DDIT3, EDEM1, ERN1, GSK3A, and ERP44 upon tunicamycin stimulation, consistent with a second-hit hypothesis.…”
Section: G0 G1mentioning
confidence: 99%